1996
DOI: 10.1002/ana.410390515
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethanol on alcohol‐responsive essential tremor: A positron emission tomography study

Abstract: We used H2 15O positron emission tomography (PET) to investigate the effect of ethyl alcohol on regional cerebral blood flow in 6 patients with alcohol-responsive essential tremor and 6 age-matched control subjects. The patients were scanned while at rest and during involuntary postural tremor of the extended right arm. Normal control subjects were scanned at rest and during passive wrist oscillation of the right arm at tremor frequency. Regional cerebral blood flow associated with these conditions was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(149 citation statements)
references
References 36 publications
7
122
1
1
Order By: Relevance
“…19 The fact that deep brain stimulation works suggests not only that multiple connected brain regions are involved in the production of the tremors but also that ET shares common neurologic substrates with Parkinson disease, for which deep brain stimulation is an established palliative procedure. Not surprisingly, alcohol relieves tremor symptoms in many patients with ET, 20 likely via the inhibition of glutamatergic pathways, but only temporarily. As the effects of ethanol wear off, the tremor symptoms actually worsen.…”
Section: Options and Reticence In Treatmentmentioning
confidence: 99%
“…19 The fact that deep brain stimulation works suggests not only that multiple connected brain regions are involved in the production of the tremors but also that ET shares common neurologic substrates with Parkinson disease, for which deep brain stimulation is an established palliative procedure. Not surprisingly, alcohol relieves tremor symptoms in many patients with ET, 20 likely via the inhibition of glutamatergic pathways, but only temporarily. As the effects of ethanol wear off, the tremor symptoms actually worsen.…”
Section: Options and Reticence In Treatmentmentioning
confidence: 99%
“…The few functional imaging studies on acute alcohol effects published so far revealed neuronal activations in the right prefrontal cortex (Tiihonen et al, 1994), in the left temporal cortex and in left striatal regions (Wang et al, 2000) and the bilateral thalamus (Boecker et al, 1996), whereas decreases were found in the occipital cortex (Volkow et al, 1990;Wang et al, 2000) and in the bilateral cerebellum (Boecker et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the investigations on acute alcohol impact on cerebral blood flow or cerebral glucose metabolism used oral alcohol administration in order to simulate 'physiological' uptake conditions (de Wit et al, 1990;Volkow et al, 1990;Schwartz et al, 1993;Boecker et al, 1996;Wang et al, 2000). The principle problems of this approach are (1) high interindividual variability of alcohol uptake by ingestion that impedes comparable arterial influx conditions and (2) impossibility to induce a fast arterial influx by means of 'normal' oral alcohol doses.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known since the 1970s from animal lesion models that interactions between the inferior olive and the cerebellum are capable of driving ET-like tremor. 46 The view that olivocerebellar fibers represent a key node in ET pathophysiology was later confirmed with PET, 26 although functional MRI studies have yielded poor evidence for intrinsic olivary dysfunction. 31 Recent evidence suggests that GABA-receptor downregulation and/ or dysfunction in the dentate nucleus (downstream of the Purkinje cells to which the inferior olive's climbing fibers project) correlates with tremor progression in a postmortem histopathological study.…”
Section: Mechanistic Understandingmentioning
confidence: 99%